2005
DOI: 10.1007/s10789-005-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melt Composition on the Luminescent Properties of Czochralski-Grown Li2B4O7 Single Crystals

Abstract: Li 2 B 4 O 7 (LTB) single crystals are grown from stoichiometric and B 2 O 3 -enriched (1.6 and 2.4 mol %) melts. At large B 2 O 3 excesses, the thermoluminescence intensity in the crystals is markedly higher, attesting to an increased density of structural defects. LTB crystals grown from B 2 O 3 -enriched melts may contain zones enriched in two types of defects. Defects of one type result from the breaking of bonds involving bridging oxygens, without significant changes in the position of neighboring atoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These properties of a shoulder peak imply that it has a complicated nature. Such maxima are claimed to root from superposition of a number of local trapping levels [6]. In a similar way, peaks observed around 300 o C are not assigned to good TL properties.…”
Section: Glow Curvementioning
confidence: 94%
See 2 more Smart Citations
“…These properties of a shoulder peak imply that it has a complicated nature. Such maxima are claimed to root from superposition of a number of local trapping levels [6]. In a similar way, peaks observed around 300 o C are not assigned to good TL properties.…”
Section: Glow Curvementioning
confidence: 94%
“…Lithium tetraborate is also known to have a high radiation resistivity and a wide operation dose range. Furthermore it is an important feature of lithium tetraborate that it is only weakly dependent on the dose on ionizing radiation energy [6].…”
Section: Properties Of Lithium Tetraboratesmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Distinct maximums at 304 and 360 nm are observed in the XL spectra for non-doped LTB single crystals [9,13]. Hence, their presence should be related to the proper defects of the crystalline lattice.…”
Section: Resultsmentioning
confidence: 95%
“…It has been found that copper addition is involved in the LTB structure at the lithium ion site [5,6]. One has to take into account that the proper genetic defects also occur in the LTB single crystals, in particular, lithium and oxygen vacancies as well as clusters related to the violation of the relation between the boron-oxygen triangles and tetrahedrons [5,9].…”
Section: Introductionmentioning
confidence: 99%